2016
DOI: 10.15252/embj.201694660
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 promotes intestinal repair through an adaptive cellular response of the epithelium

Abstract: Adaptive cellular responses are often required during wound repair. Following disruption of the intestinal epithelium, wound-associated epithelial (WAE) cells form the initial barrier over the wound. Our goal was to determine the critical factor that promotes WAE cell differentiation. Using an adaptation of our in vitro primary epithelial cell culture system, we found that prostaglandin E2 (PGE 2 ) signaling through one of its receptors, Ptger4, was sufficient to drive a differentiation state morphologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
200
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(227 citation statements)
references
References 93 publications
(158 reference statements)
23
200
3
1
Order By: Relevance
“…A defining feature of barrier re-establishment is the formation of a monolayer of post-mitotic WAE cells that are produced by stem/progenitor cells in crypts adjacent to wound (Figure S1A) (Manieri et al, 2012). WAE cell formation is dependent on PGE2 signaling to the epithelium through PTGER4 (Miyoshi et al, 2017). The next phase (days~4–8) is wound channel formation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A defining feature of barrier re-establishment is the formation of a monolayer of post-mitotic WAE cells that are produced by stem/progenitor cells in crypts adjacent to wound (Figure S1A) (Manieri et al, 2012). WAE cell formation is dependent on PGE2 signaling to the epithelium through PTGER4 (Miyoshi et al, 2017). The next phase (days~4–8) is wound channel formation.…”
Section: Resultsmentioning
confidence: 99%
“…To further test the role of timing, we performed DCA reconstitution from day 0-day 3 in vancomycin pre-treated mice and analyzed wounds at day 4 post-injury. We used a previously established method of analyzing wounds at day 4 from whole mount images (Miyoshi et al, 2017) and found that this treatment significantly impaired barrier re-establishment associated with reduced PGE2 levels (Figure S5C–E). Taken together, these findings confirm that the timing of DCA generation is crucial for transition from barrier re-establishment to crypt regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations